Neuropeptide trefoil factor 3 attenuates naloxone-precipitated withdrawal in morphine-dependent mice - Ping Wu; Hai-Shui Shi; Yi-Xiao Luo; Ruo-Xi Zhang; Jia-Li Li; Jie Shi; Lin Lu; Wei-Li Zhu (Psychopharmacology, 2014)

Association of IL-18 promoter gene polymorphisms with rheumatoid arthritis: a meta-analysis - Li-Ping Cai; Li-Juan Zhou; Shun-Yu Lu; Ying-E Liang; Xiao-Ying Chen; Lin Liu; Jun Lin (Molecular Biology Reports, 2014)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Isolation and molecular characterization of an ethylene response factor NtERF1-1 in Nicotiana tabacum cv. Xanthi - Jun-Shan Gao; Li Hu; Peng Xie; Yan Meng; Yong-Ping Cai; Yi Lin (Journal of Biosciences, 2014)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Development, characterization and cross-species amplification of new microsatellite primers from an endemic species Cinnamomum kanehirae (Lauraceae) in Taiwan - Kuo-Hsiang Hung; Chia-Hung Lin; Huei-Chuan Shih; Yu-Chung Chiang; Li-Ping Ju (Conservation Genetics Resources, 2014)

Local adaptation and phenotypic plasticity both occurred in Wedelia trilobata invasion across a tropical island - Chun-Can Si; Zhi-Cong Dai; Ying Lin; Shan-Shan Qi; Ping Huang; Shi-Li Miao; Dao-Lin Du (Biological Invasions, 2014)

Bio-beads with immobilized anaerobic bacteria, zero-valent iron, and active carbon for the removal of trichloroethane from groundwater - Ya-Zhen Zhou; Jie Yang; Xiao-Li Wang; Yue-Qing Pan; Hui Li; Dong Zhou; Yong-Di Liu; Ping Wang; Ji-Dong Gu; Qiang Lu; Yue-Feng Qiu; Kuang-Fei Lin (Environmental Science and Pollution Research, 2014)

The phosphorylation of an actin depolymerizing factor by a calcium-dependent protein kinase regulates cotton fiber elongation - Quan-Sheng Huang; Xun-Ji Chen; Jian-Ping Li; Xiao-Yan Hao; Guo Chen; Zumuremu; Lin Shao (Acta Physiologiae Plantarum, 2014)

The Melanogenesis-Inhibitory Effect and the Percutaneous Formulation of Ginsenoside Rb1 - Lin Wang; Ai-Ping Lu; Zhi-Ling Yu; Ricky N. S. Wong; Zhao-Xiang Bian; Hoi-Hin Kwok; Patrick Ying-Kit Yue; Li-Min Zhou; HuBiao Chen; Min Xu; Zhijun Yang (AAPS PharmSciTech, 2014)

Influence of gene flow on divergence dating – implications for the speciation history of Takydromus grass lizards - Shu‐Ping Tseng; Shou‐Hsien Li; Chia‐Hung Hsieh; Hurng‐Yi Wang; Si‐Min Lin (Molecular Ecology, 2014)
Dating the time of divergence and understanding speciation processes are central to the study of the evolutionary history of organisms but are notoriously difficult. The difficulty is largely rooted in variations in the ancestral population size or in the genealogy variation across loci. To depict the speciation processes and divergence histories of three monophyletic Takydromus species endemic to Taiwan, we sequenced 20 nuclear loci and combined with one mitochondrial locus published in GenBank. They were analysed by a multispecies coalescent approach within a Bayesian framework. Divergence dating based on the gene tree approach showed high variation among loci, and the divergence was estimated at an earlier date than when derived by the species‐tree approach. To test whether variations in the ancestral population size accounted for the majority of this variation, we conducted computer inferences using isolation‐with‐migration ( IM ) and approximate Bayesian computation ( ABC ) frameworks. The results revealed that gene flow during the early stage of speciation was strongly favoured over the isolation model, and the initiation of the speciation process was far earlier than the dates estimated by gene‐ and species‐based divergence dating. Due to their limited dispersal ability, it is suggested that geographical isolation may have played a major role in the divergence of these Takydromus species. Nevertheless, this study reveals a more complex situation and demonstrates that gene flow during the speciation process cannot be overlooked and may have a great impact on divergence dating. By using multilocus data and incorporating Bayesian coalescence approaches, we provide a more biologically realistic framework for delineating the divergence history of Takydromus .

Dysregulation of vitamin D metabolism in the brain and myocardium of rats following prolonged exposure to dexamethasone - Pei Jiang; Ying Xue; Huan-De Li; Yi-Ping Liu; Hua-Lin Cai; Mi-Mi Tang; Li-Hong Zhang (Psychopharmacology, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Indian Ocean variability in the CMIP5 multi-model ensemble: the zonal dipole mode - Lin Liu; Shang-Ping Xie; Xiao-Tong Zheng; Tim Li; Yan Du; Gang Huang; Wei-Dong Yu (Climate Dynamics, 2014)

Differential role of Rac in the basolateral amygdala and cornu ammonis 1 in the reconsolidation of auditory and contextual Pavlovian fear memory in rats - Ping Wu; Zeng-Bo Ding; Shi-Qiu Meng; Hao-Wei Shen; Shi-Chao Sun; Yi-Xiao Luo; Jian-Feng Liu; Lin Lu; Wei-Li Zhu; Jie Shi (Psychopharmacology, 2014)

Extensive Female-Mediated Gene Flow and Low Phylogeography Among Seventeen Goat Breeds in Southwest China - Wei Zhao; Tao Zhong; Lin Jie Wang; Li Li; Hong Ping Zhang (Biochemical Genetics, 2014)

A new epimer of ocotillol from stems and leaves of American ginseng - Liu Han; Mei-Yu Lin; Qian Zheng; Hai-Yu Liu; Hai-Yan Liu; Gang Dong; Jin-Ping Liu; Ping-Ya Li (Natural Product Research, 2014)

High-level soluble expression of the hemA gene from Rhodobacter capsulatus and comparative study of its enzymatic properties - Jia-wei Lou; Li Zhu; Mian-bin Wu; Li-rong Yang; Jian-ping Lin; Pei-lin Cen (Journal of Zhejiang University-SCIENCE B, 2014)

Systematic position of Cyathocline Cass. (Asteraceae): evidences from molecular, cytological and morphological data - Wei-Ping Li; Feng-Ming Qian; Xiu-Lin Yang; San-Mao Chen (Plant Systematics and Evolution, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Using ADABOOST and Rough Set Theory for Predicting Debris Flow Disaster - Ping-Feng Pai; Lan-Lin Li; Wei-Zhan Hung; Kuo-Ping Lin (Water Resources Management, 2014)

Stripe rust resistance and genes in Chinese wheat cultivars and breeding lines - Qing-Dong Zeng; De-Jun Han; Qi-Lin Wang; Feng-Ping Yuan; Jian-Hui Wu; Li Zhang; Xiao-Jie Wang; Li-Li Huang; Xian-Ming Chen; Zhen-Sheng Kang (Euphytica, 2014)
Stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is one of the most important diseases on wheat in China. To assess resistance in wheat cultivars and breeding lines in China, 330 leading cultivars and 164 advanced breeding lines were evaluated with stripe rust. In the greenhouse tests, seedlings of the entries were inoculated separately with several Pst pathotypes. In the field tests, the entries were evaluated for stripe rust resistance in Yangling, Shaanxi Province artificially inoculated and in Tianshui, Gansu Province under natural infection of Pst . The oversummering/wintering and spring epidemic zones of resistance genes were postulated using molecular markers for Yr5 , Yr9 , Yr10 , Yr15 , Yr17 , Yr18 , and Yr26 , in combination with resistance spectra. Out of the 494 wheat entries, 16 (3.24 %) entries had all-stage resistance (ASR) in all race tests, 99 (20.04 %) had adult-plant resistance (APR), 28 (5.67 %) were considered to have slow-rusting (SR), and 351 (71.05 %) were susceptible to one or more races in both seedling and adult-plant stages. Advanced breeding lines had a higher percentage (37.2 %) of resistant entries (The sum of ASR, APR and SR) than leading cultivars (24.85 %). Among the epidemic regions, southern Gansu had a higher percentage of resistant entries than any other regions. Based on stripe rust reactions and molecular markers, two cultivars were found to possibly have Yr5 while no entries have Yr10 or Yr15 . Resistance genes Yr9 , Yr17 , Yr18 , and Yr26 were found in 134 (29.4 %), 45 (9.1 %), 10 (2 %), and 15 (3 %) entries, respectively.

HMGB1 Contributes to Regeneration After Spinal Cord Injury in Adult Zebrafish - Ping Fang; Hong-Chao Pan; Stanley Li Lin; Wen-Qing Zhang; Heikki Rauvala; Melitta Schachner; Yan-Qin Shen (Molecular Neurobiology, 2014)

Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2014)

Phylogeography of Hipposideros armiger (Chiroptera: Hipposideridae) in the Oriental Region: the contribution of multiple Pleistocene glacial refugia and intrinsic factors to contemporary population genetic structure - Ai‐Qing Lin; Gabor Csorba; Lin‐Feng Li; Ting‐Lei Jiang; Guan‐Jun Lu; Vu Dinh Thong; Pipat Soisook; Ke‐Ping Sun; Jiang Feng (Journal of Biogeography, 2014)
Aim The goals of our study were to assess the population history and genetic structure of the widespread bat H ipposideros armiger , and to evaluate the effect of palaeoclimatic changes and dispersal patterns on this species. Location S outh C hina, mainland S outheast A sia and the S outh H imalayas. Methods We amplified two mitochondrial DNA (mt DNA ) regions (cyt b and D ‐loop) and seven nuclear microsatellite loci (n SSR s) from 216 individuals of H . armiger . To examine the evolutionary history of this species, we constructed maximum likelihood and Bayesian phylogenetic trees based on the two mt DNA regions. From the mt DNA and/or n SSR data, we assessed population genetic structure using analysis of molecular variance ( AMOVA ) and median‐joining network and structure analyses. We also estimated demographic history and gene flow using a B ayesian skyline plot and the program I Ma 2. Results Phylogenetic and median‐joining network analyses revealed that H . armiger comprises two distinct mt DNA clades divided into seven subclades. The results of AMOVA suggested strong population genetic structure based on mt DNA , but weak structure based on n SSR s. structure analysis identified three population clusters and also showed weak genetic structure at the nuclear level. Demographic analyses revealed two population expansion events c . 0.62 Ma and c . 0.25 Ma. The basic phylogeographical structure of H . armiger was established by 0.24 Ma. I Ma 2 analysis demonstrated that substantial gene flow has occurred between different regions since then. Additionally, non‐significant population structure and significant gene flow were detected between T aiwan and H ainan island populations and those from mainland C hina. Main conclusions Our results suggest that divergence and population expansion of H . armiger occurred in association with P leistocene climatic changes and that multiple refugia may have existed for this species. Post‐glacial male‐biased dispersal was likely to be the primary contributor to the contemporary genetic structure of H . armiger populations. Gene flow may have contributed greatly to the genetic structure of insular populations and populations from mainland C hina.